Colonial Caring A History of Colonial and Post-colonial Nursing - Hawkins, Sue; Sweet, Helen (Nursing History and Humanities, 2014)
From the height of colonialism in the mid-nineteenth century, through to the aftermath of the Second World War, nurses have been at the heart of colonial projects. They were ideally placed to insinuate the 'improving' culture of their employers into the local communities they served, and travelled in droves to far-flung parts of the globe to serve their country. Issues of gender, class and race permeate this book, as the complex relationships between nurses, their medical colleagues, governments and the populations they nursed are examined in detail, using case studies which draw on exciting new sources. Many of the chapters are based on first-hand accounts of nurses and reveal that not all were motivated by patriotic vigour or altruism, but went out in search of adventure. The book will be an essential read for colonial historians, as well as historians of gender and ethnicity.